Les Ottomans et le temps. - Georgeon, François (Ottoman Empire and its heritage., 2011)
This work offers several new perspectives on the phenomenon of time in the Ottoman era and space, and its place in the lives of Ottoman subjects. The collected articles suggest that temporality in the Ottoman Empire was not the same in all cities, nor even in campaigns. Moreover, the Ottoman domains were so vast that its subjects' appreciation of time also took on multiple forms from one region of the empire to another. Temporality also varied according to social, professional, and religious categories.